2022
DOI: 10.1080/10717544.2022.2139021
|View full text |Cite
|
Sign up to set email alerts
|

Design and applications of liposome-in-gel as carriers for cancer therapy

Abstract: Cancer has long been a hot research topic, and recent years have witnessed the incidence of cancer trending toward younger individuals with great socioeconomic burden. Even with surgery, therapeutic agents serve as the mainstay to combat cancer in the clinic. Intensive research on nanomaterials can overcome the shortcomings of conventional drug delivery approaches, such as the lack of selectivity for targeted regions, poor stability against degradation, and uncontrolled drug release behavior. Over the years, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…The viscosity of ELE-GA/NGO-Lip-gel was constant when the temperature was about 25°C and began to surge at 30°C and increased slowly at 37°C (Figure 2(g)). 34 The particle sizes of ELE-GA/NGO-Lip and ELE-GA/NGO-Lip-gel were 141.7 ± 0.75 nm (PDI = 0.13, Figure 2(h)) and 171.0 ± 0.25 nm (PDI = 0.13) (Figure 2(i)), respectively. Zeta potential of ELE-GA/NGO-Lip and ELE-GA/NGO-Lip-gel were −25.00 ± 0.23 mV and 8.06 ± 4.9 mV, respectively.
Figure 2.Characterization of ELE-GA/NGO-Lip-gel.
…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The viscosity of ELE-GA/NGO-Lip-gel was constant when the temperature was about 25°C and began to surge at 30°C and increased slowly at 37°C (Figure 2(g)). 34 The particle sizes of ELE-GA/NGO-Lip and ELE-GA/NGO-Lip-gel were 141.7 ± 0.75 nm (PDI = 0.13, Figure 2(h)) and 171.0 ± 0.25 nm (PDI = 0.13) (Figure 2(i)), respectively. Zeta potential of ELE-GA/NGO-Lip and ELE-GA/NGO-Lip-gel were −25.00 ± 0.23 mV and 8.06 ± 4.9 mV, respectively.
Figure 2.Characterization of ELE-GA/NGO-Lip-gel.
…”
Section: Resultsmentioning
confidence: 96%
“…ELE loading on GA/NGO was possibly through π-π stacking and electrostatic interactions, 32 ELE-GA/NGO and free ELE were respectively entrapped into the inner aqueous core and membrane regions of the liposomes, then ELE-GA/NGO-Lip was incorporated into the hydrogel substrates to form ELE-GA/NGO-Lip-gel. 33,34 The experimental results showed that ELE-GA/NGO-Lip-gel had good temperature sensitivity and biodegradability, and could be used for local injection of tumor. Then, the antitumor activity of ELE-GA/NGO-Lip-gel with 808 nm (2.5 W/cm 2 ) NIR laser irradiation was investigated in SMMC-7721 cells in vitro, including cytotoxicity assay, cell migration assay and cell uptake assay, etc.…”
Section: Introductionmentioning
confidence: 99%
“…32 In recent years, nanoparticle drug delivery systems in TDDS have shown significant potential for targeted drug delivery, increased drug stability, prolonged drug action, and improved bioavailability. [33][34][35][36][37][38] Several nanocarrier formulations have been developed to enhance transdermal drug delivery, including liposomes, ethosomes, transfersomes, polymeric micelles, selfnanoemulsifying drug delivery system (SNEDDS), solid lipid nanoparticles (SLN), nanostructured lipid carriers (NLCs), and polymeric nanoparticles. [39][40][41][42][43][44] Despite the growing popularity of TDDS, there have been limited developments in formulations specifically for CBD.…”
Section: Introductionmentioning
confidence: 99%
“…Isotonic and isohydric liposomal dispersions—also without presence of active ingredients—can be successfully applied in selected cases, e.g., as artificial tears for dry eye syndrome [ 25 , 26 , 27 ]. In other cases, according to the needs, the encapsulation of appropriate drug molecules can be necessary [ 28 , 29 , 30 , 31 , 32 ]. On the basis of their physicochemical properties, active ingredients can be encapsulated into the aqueous phase of liposomes or can be located between the apolar fatty acids or bound to the polar lipid heads of the bilayer [ 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…If the liposomal dispersion possesses the viscoelastic property, it may provide additional benefits to its therapeutic effect. Therefore, understanding and knowing the factors influencing viscoelasticity in the case of various dosage forms—among others, liposomal-based drug delivery systems—is crucial for formulation development aspects [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%